Examining Successful Management Practices Among Senior Women Using Artificial Intelligence Technology - Gilliam, Leslie; Lao, Teresa; Nweke, Chikwendu (Journal of Strategic Innovation and Sustainability, 2024)
Artificial intelligence (AI) technology innovations can intensify the digital ecosystem affecting management practices and the quality of life for female senior business leaders in the United States. The purpose of this qualitative, transcendental phenomenology study was to examine the lived experiences that some female senior business leaders, ages 55 - 95, face using AI technology in decision-making. The conceptual framework are Technology Acceptance Model (TAM) and the Mindspace Model. Data was collected through interviews with 12 successful female senior business leaders from nine industries in the US. The Van Kaam method, supported by Moustakas’ theoretical process, was used to analyze the data. Descriptive and inductive coding was used to categorize the themes: (a) AI technology is beneficial, (b) leadership and change management, (c) technology adaptation and acceptance, (d) decision-making and communication, and (e) information sharing and privacy. This study contributes to positive social change as a benefit to seniors by strengthening their AI technology decision-making practices, leadership, and community awareness in addition to influencing positive social change across management platforms.